The Meaning of Political Conflict in the Ketoprak “Satru Ing Ngepal” - Sahid, Nur; Junaidi, Junaidi; Iswantara, Nur (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
This study aims to analyze the meaning of signs related to political conflict between characters in sineprak “Satru Ing Ngepal” (SIN). The political conflicts between these figures will be analyzed for their meaning by relating them to the social-historical context of Indonesia in the New Order and Reformation Eras. The research uses a theatrical semiotic theory approach, dividing theatrical performances into 13 sign systems. Signs related to political conflict between figures will be analyzed denotatively and connotatively. The content analysis method from Kriipendorf was used to analyze the data. The results of this study indicate that Senopati’s political conflict with Mangir semiotically refers to the meaning of the political conflict between the New Order and Reform rulers and the opposition. The enmity between Senopati, Juru Mertani, and Mangir refers to the meaning of the conflict between Wiranto and Prabowo Subianto. Pembayun’s marriage to Mangir means Prabowo Subianto joining President Jokowi’s government for 2019-2024. Pembayun’s courage to fight for Mataram peace with Mangir’s fief land refers to RA Kartini’s emancipation.